3D printed peripheral vascular stents based on degradable poly(trimethylene carbonate‐b‐(L‐lactide‐ran‐glycolide)) terpolymer. (11th February 2023) - Ni, Na; Fan, Tiantang; Ye, Wuyou; Xia, Qi; Liu, Dongyang; Qin, Jingwen; Fan, Zhongyong; Liu, Qing
Abstract: Poly(L ‐lactic acid) (PLLA) is a biocompatible material and has found its application in bioresorbable vascular stents (BVS). However, the crystallization of pure PLLA makes it brittle as a medical implant device. In this work, the biodegradable poly(1, 3‐trimethylene carbonate‐ b ‐(L ‐lactide‐ ran ‐glycolide acid)) (PTLG) terpolymers with improved mechanical performance were developed and processed into peripheral vascular stents by a novel 3D 4‐axial printing technology. The PTLG terpolymers were successfully synthesized by ring‐opening copolymerization of L ‐lactic acid (LLA), 1, 3‐trimethylene carbonate (PTMC) and glycolide acid (GA) units. The crystallinity and mechanical properties of the PTLG terpolymers with various degradation rate depends on the chain sequence structure and the component contents. Compared with the stent prepared by laser engraving, the peripheral vascular stent prepared by the 3D 4‐axial printing technology exhibit a finer structure and smoother strut surface. It was found that both the strut diameters and the molecular weight of PTMC affect the radial force of the stents and that the apparent activation energy of thermal decomposition of the stents is mainly influenced by the molecular weight of PTMC and the component ratio. Therefore, the addition of the PTMC segment can effectively improve the flexibility of the PTLG terpolymer stent and the 3D printed PTLG terpolymer‐based stent. Furthermore, CCK‐8 and live/dead staining suggested that the stents have good biocompatibility.